Unfortunate emigrants: narratives of the Donner Party - Johnson, Kristin, editor; Utah State University Press, publisher (Colorado State University. Libraries, 1996)
The story of the Donner Party remains one of the most tragic and compelling in pioneer history. Johnson gathers many rare early narratives detailing the participants' trying experiences into one of the most accurate accounts to date of this disastrous event.
J. Quinn Thornton -- From Oregon and California in 1848 -- Lilburn W. Boggs -- Immigrants to California -- Mary Ann Graves -- Letter from California -- H.A. Wise -- From Los Gringos -- Eliza W. Farnham -- From California, in-doors and out -- J. Ross Browne -- From "A dangerous journey" -- Frances H. McDougall -- The Donner tragedy: a thrilling chapter in our pioneer history -- James F. Reed -- The snow-bound, starved emigrants of 1846 -- William McCutchen -- Statement of William McCutchen -- Frances H. McDougall -- The Donner Tragedy once more: reply to Mr. Reed -- W.C. Graves -- Crossing the plains in '46 -- Jacob Wright Harlan -- From California '46 to '88 -- Virginia Reed Murphy -- Across the plains in the Donner Party (1846) -- Edna Maybelle Sherwood -- Tragic story of the Donner Party -- Roster of the Donner Party.
Keywords: Donner Party; Overland journeys to the Pacific